Genomic alterations in plasma DNA from patients with metastasized prostate cancer receiving abiraterone or enzalutamide. Issue 5 (10th April 2018) - Belic, Jelena; Graf, Ricarda; Bauernhofer, Thomas; Cherkas, Yauheniya; Ulz, Peter; Waldispuehl‐Geigl, Julie; Perakis, Samantha; Gormley, Michael; Patel, Jaymala; Li, Weimin; Geigl, Jochen B.; Smirnov, Denis; et al.
Abstract : In patients with metastatic castrate‐resistant prostate cancer (mCRPC), circulating tumor DNA (ctDNA) analysis offers novel opportunities for the development of non‐invasive biomarkers informative of treatment response with novel agents targeting the androgen‐receptor (AR) pathway, such as abiraterone or enzalutamide. However, the relationship between ctDNA abundance, detectable somatic genomic alterations and clinical progression of mCRPC remains unexplored. Our study aimed to investigate changes in plasma DNA during disease progression and their associations with clinical variables in mCRPC patients. We analyzed ctDNA in two cohorts including 94 plasma samples from 25 treatment courses (23 patients) and 334 plasma samples from 125 patients, respectively. We conducted whole‐genome sequencing (plasma‐Seq) for genome‐wide profiling of somatic copy number alterations and targeted sequencing of 31 prostate cancer‐associated genes. The combination of plasma‐Seq with targeted AR analyses identified prostate cancer‐related genomic alterations in 16 of 25 (64%) treatment courses in the first cohort, in which we demonstrated that AR amplification does not always correlate with poor abiraterone and enzalutamide therapy outcome. As we observed a wide variability of ctDNA levels, we evaluated ctDNA levels and their association with clinical parameters and included the second, larger cohort for these analyses. Employing altogether 428 longitudinal plasma samples from 148 patients, we identified the presence of bone metastases, increased lactate dehydrogenase and prostate‐specific antigen (PSA) as having the strongest association with high ctDNA levels. In summary, ctDNA alterations are observable in the majority of patients with mCRPC and may eventually be useful to guide clinical decision‐making in this setting. Abstract : What's new? Despite the development of novel androgen receptor (AR) axis‐targeting agents, prognosis remains poor for patients with metastatic prostate cancer. Hence, there is urgent need to develop biomarkers to optimize therapy selection. In this study, therapy‐related alterations within tumor genomes were captured via analyses of circulating tumor DNA (ctDNA). Analyses show that high ctDNA levels are strongly associated with bone metastases and elevated prostate‐specific antigen and lactate dehydrogenase levels. Meanwhile, investigation of AR amplification revealed inconsistent associations with poor outcome in patients treated with AR axis‐targeting drugs. The findings suggest that ctDNA content is a valuable biomarker in prostate cancer.